Analyzing RNA‐Protein Interactions by Cross‐Link Rates and CLIP‐seq Libraries. Issue 1 (27th January 2023) - Porter, Douglas F.; Garg, Raghav M.; Meyers, Robin M.; Miao, Weili; Ducoli, Luca; Zarnegar, Brian J.; Khavari, Paul A.
Abstract: UV cross‐linking‐based methods are the most common tool to explore in vivo RNA‐protein interactions. UV cross‐linking enables the freezing of direct interactions in the cell, which can then be mapped by high‐throughput sequencing through a family of methods termed CLIP‐seq. CLIP‐seq measures the distribution of cross‐link events by purifying a protein of interest and sequencing the covalently bound RNA fragments. However, there are disagreements and ambiguities as to which proteins are RNA‐binding proteins and what interactions are significant as all proteins contact all RNAs at some frequency. Here we describe a protocol for both determining RNA‐protein interactions through a combination of RNA library preparation and the measurement of absolute cross‐link rates, which helps determine what proteins are RNA‐binding proteins and what interactions are significant. This protocol, comprising an updated form of the easyCLIP protocol, describes guidelines for RNA library preparation, oligo and protein standard construction, and the measurement of cross‐link rates. These methods are easily visualizable through their fluorescent labels and can be adapted to study RNA‐binding properties of both functional, high affinity RNA‐binding proteins, and the accidental RNA interactions of non‐RNA‐binding proteins. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : RNA library construction Basic Protocol 2 : Determining UV cross‐link rates Support Protocol 1 : Cross‐linking and lysing cells Support Protocol 2 : Adapter preparation Support Protocol 3 : Preparation of cross‐linked RBP standard